A theology of the Greek version of Proverbs - Cook, Johann (HTS teologiese studies, 2015)
This contribution demonstrates that it is possible to formulate a theology of LXX Proverbs. It limits itself to a pilot study of three passages, Chapters 1, 2 and 8. A contextual approach is followed and the following conclusions, that have implications for a theology, are reached:1. 1:1–7 indicates what Proverbs is not, i.e. speculative philosophical ideas 2. Chapter 2 demonstrates that the wisdom is foreign wisdom – the Hellenism of the day 3. Sophia in chapter 8 has a subordinate role in relation to God.